Molecular docking of Vitamin D3 Receptor (VDR) with potential herbal substance as ligand to prevent excessive hair loss in menopausal women - Parawangsa, Aditya; Sugito, Syailendra Karuna; Ayu Ananda Latifa, Ariestiana; Dinda Safira, Nadya; Ayuthaya, Shafa; Rahmalia Az Zahra, Raissa (Indonesian Journal of Medical Chemistry and Bioinformatics, 2022)
Hair loss is commonly found in menopausal women. Hair loss is one of the consequences of hormonal dynamics when a woman stops having menstrual cycle, which affect calcium and vitamin D level in the body. Although it is clear enough that hormonal adjustment is required, older people and another sociodemographic factor prefer herbal-based therapeutic rather than synthetic-based due to tradition and positive experience factors. This study is an in-silico study which aims to point out the possible ligand candidates that can work as Vitamin D Receptor (VDR) agonists. We perform molecular docking using Autodock version 4.2 with the criteria of Lamarckian GA. VDR (PDB ID: 1TXI) was docked with ten compounds and one native ligand, then analyzed using Autodock 4.2. Dolichosterone, Gartanin, and (-)-Matairesinol, Luteolin, 5-HETE, Sinapyl glucoside, and geraniol, in order shows smallest to bigger binding energy when simulated in the software (-9.72, -7.70, -7.20, -6.88, -5.76, -5.71 kcal/mol). Thus, we found that these compounds are potential to become VDR agonist. Further research is still required to determine each compound drug potential and maximize therapeutic concentration for medicinal purposes.